(untitled) (The International Journal for Scientific Research, 2024)
Sports activities of all kinds have received generous support from the government of the Kingdom of Saudi Arabia, the impact of which is evident in hosting various types of sports activities and organizing them with the latest means and technologies, in addition to the strategic direction in attracting and attracting international professionals, which requires creating a competitive advantage capable of attracting them, and therefore artificial intelligence can play this role. The sports environment was safe and safety enhanced by the latest technologies and tools whenever it affected in one way or another the recruitment and decision to move to local Saudi clubs. We have a good example of the recent historical deals. Due to the importance of this topic, the title of this study was chosen, “The contribution of artificial intelligence to the safety of players.” This study aimed to analyze the benefits of artificial intelligence and its contributions to the safety of football players by using technology to predict injuries and develop plans designed to suit the needs. The individuality of each player. In this study, we will discuss the definition of many terms such as performance analysis, prediction, etc. The researcher in this study used the descriptive analytical method, which is defined as the method that includes studying the current facts related to the nature of a phenomenon, a situation, a group of people, or a group of people. Events or a group of situations. Descriptive studies are not limited to knowing the characteristics of the phenomenon, but go beyond that to knowing the variables and factors that cause the phenomenon to exist. The study population constitutes the relevant parties, including players, technical, administrative and medical personnel, and sports officials, in which Saudi football stadiums were targeted in the year 202. The sample size ranges from 50 people. The researcher used an electronic questionnaire tool to collect data. Perhaps the most prominent results that the researcher reached is the existence of a positive relationship between the use of artificial intelligence and the safety of players. The use of technology has had an impact on reducing the rate of injuries by predicting them, accelerating recovery processes, and significantly improving players’ performance by developing strategies for each player according to artificial intelligence data and analyses. However, there were reservations regarding data privacy and protection.